2006
DOI: 10.1021/jp0531053
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of the Effect of the Composition of Calcium Alumino-Silicate Intergranular Films on Alumina Grain Growth

Abstract: Molecular dynamics simulations were performed to study the effect of the composition of the intergranular film (IGF) on anisotropic and isotropic grain growth in R-Al 2 O 3 . In the simulations, the IGF is formed while in contact with two differently oriented alumina crystals, with the alumina (0001) basal plane on one side and the (112 h0) prism plane on the other. Five different compositions in the IGFs were studied. Results show preferential growth along the [112 h0] of the (112 h0) surface in comparison to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
25
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 39 publications
6
25
0
Order By: Relevance
“…The modified-BMH potential was employed to describe the atomic behavior of silicon oxide, which was developed by Garofalini et al [16,17,[28][29][30], to fit into certain interatomic angles and coulombic forces of the amorphous phase. The total energy of the system V is modeled as a sum of the twobody and three-body interaction terms as follows:…”
Section: Potential Energy Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The modified-BMH potential was employed to describe the atomic behavior of silicon oxide, which was developed by Garofalini et al [16,17,[28][29][30], to fit into certain interatomic angles and coulombic forces of the amorphous phase. The total energy of the system V is modeled as a sum of the twobody and three-body interaction terms as follows:…”
Section: Potential Energy Functionmentioning
confidence: 99%
“…Note that the modified-BMH potential was originally developed to characterize the amorphous silicon oxide [16,17] by considering the angle dependency in describing interatomic forces. It is versatile in including other elements, such as nitrogen and aluminum [28][29][30]. It should also be pointed out that basic studies with computational methods using MD techniques have been seldom performed, especially on crystalline phases and grain boundaries, despite the great interest in SiO 2 materials.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the low solubility limit of common impurities in alumina such as calcia and silica, liquid phases with Ca/Si concentrations far in excess of the bulk level form at grain boundaries 3–6 that preferentially adsorb to certain crystalline planes 7,8 . Computational studies have been able to simulate this behavior and offer a geometric and energetic explanation for this preferential adsorption and the anisotropic grain growth that results; 9 however, considerably less attention has been paid to the opposite effect of preferential dissolution of crystallographic planes that are commonly exposed to the liquid phase during the sintering process.…”
Section: Introductionmentioning
confidence: 99%
“…In order to address these concerns, the molecular dynamics simulation technique was applied to examine the dissolution behavior of differently oriented alumina crystals into silicate melts of varying composition using interatomic potentials applied in previous computational studies of grain growth 9 …”
Section: Introductionmentioning
confidence: 99%
“…It was also found that the films' properties can change depending on structure and thickness of the film. However, due to microscopy limitations the structure of the film was not fully resolved and considered to be mainly disordered (amorphous), although order was predicted in the films from both theoretical models and simulations [2]. Relatively recently IGFs were discovered to also exist at metal-ceramic interfaces, and the fundamental questions regarding the structure of the film remain the same.…”
mentioning
confidence: 99%